2020
DOI: 10.1186/s13000-020-00979-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic perspectives of PD-L1 combined with tumor-infiltrating lymphocytes, Epstein-Barr virus, and microsatellite instability in gastric carcinomas

Abstract: Background The prognostic potential of PD-L1 is currently unclear in gastric carcinomas, although the immune checkpoint PD-1/PD-L1 inhibitors have produced promising results in clinical trials. Methods We explored the prognostic implications of programmed death ligand 1 (PD-L1) in 514 consecutive surgically-resected gastric carcinomas. Overall survival and recurrence-free survival were evaluated. Immunohistochemistry for PD-L1, CD8, FOXP3, and PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 47 publications
6
29
0
Order By: Relevance
“… 35 Combination of PD-L1 expression in cancer cells and the number of infiltrating CTLs predicts patient prognosis in gastric cancer. 38 PD-1 positive T cell characteristics, including cytokine and chemokine productions, are different in the tumor (TIL) and in the peripheral blood in lung cancer. 39 Positive stainings of PD-L1 in cancer cells and PD-1 in lymphocytes are associated with aggressive cancer biology, on the other hand, they are also associated with increased pathological complete response to the neoadjuvant chemotherapy in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Combination of PD-L1 expression in cancer cells and the number of infiltrating CTLs predicts patient prognosis in gastric cancer. 38 PD-1 positive T cell characteristics, including cytokine and chemokine productions, are different in the tumor (TIL) and in the peripheral blood in lung cancer. 39 Positive stainings of PD-L1 in cancer cells and PD-1 in lymphocytes are associated with aggressive cancer biology, on the other hand, they are also associated with increased pathological complete response to the neoadjuvant chemotherapy in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of De Rosa et al (2018), only 3% PD-L1 + cases were found in MSS/EBV − subgroup and a case was considered positive if membrane immunostaining was present in at least 5% of tumor cells, independently of the intensity. Choi et al (2020) found 14% PD-L1-positive cases in MSS/EBV − when considering both staining intensity and percentage of stained tumor cells, and any membranous staining was regarded as positive expression. In the present study, a higher proportion of PD-L1 + cases in MSS/EBV − group (35%) are reported when scoring PD-L1 expression on the basis of both the intensity and percentage of PD-L1-positive TCs and considering both cell membrane and cytoplasm staining.…”
Section: Discussionmentioning
confidence: 99%
“…A review of PD-L1 expression in gastric cancer ( Vrna et al, 2018 ) showed that the percentage of PD-L1 + in the TCs ranges from 9% to 49.1% (most of the trials were performed in Asian populations), similar to our results (41.2% in TCs). Previous studies have demonstrated a mutually exclusive relationship between GCs that were EBV-positive and deemed to have MSI ( Choi et al, 2020 ). However, two cases representing both MSI and EBV-positive were observed in a recent study (2/287, 0.70%) ( Pereira et al, 2018 ) and in our study (2/226, 0.88%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, targeting the immune escape mechanisms of cancer cells and immune checkpoint inhibitor treatment have become the standard for cancer therapy [ 40 ]. Both a high frequency of tumor-infiltrative T cells and PD-1 expression are thought to be potential biomarkers for indicating a response to immune checkpoint inhibitors [ 41 , 42 ]. The high frequency of tumor-infiltrating T cells (revealed by immunostaining of CD8) and the high frequency of PD-1 expression in tumor-infiltrating lymphocytes in the current cases of RSEAC suggest that immune checkpoint inhibitor therapy could also be effective for patients with RSEAC.…”
Section: Discussionmentioning
confidence: 99%